2016
DOI: 10.5812/traumamon.26117
|View full text |Cite
|
Sign up to set email alerts
|

A Framework for the Calculation of Direct and Indirect Costs of Accidents and Its Application to Incidents Occurring in Iran’s Construction Industry in 2013

Abstract: Background: Occupational accidents represent one of the major problems in developing and developed countries. Deaths caused by occupational accidents result in loss of life, lost working hours, and related costs. These accidents create a lot of waste for the community and labor organizations. Moreover, they result in socioeconomic losses such as disability, loss of work time, and increased medical care expenses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 15 publications
1
5
1
Order By: Relevance
“…Therefore, studying the various causes and factors affecting the occurrence of occupational accidents and paying attention to the effective factors and causes in the occurrence of these accidents in any society can be specific to that work environment and occupational community. Consistent with various studies (27)(28)(29), this study revealed that although the index of non-organizational factors was estimated to be average, a significant relationship was observed between that and 10 parameters related to occupational accidents. Also, this factor analysis indicated that this index was directly related to some parameters of accidents and inversely related to others.…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, studying the various causes and factors affecting the occurrence of occupational accidents and paying attention to the effective factors and causes in the occurrence of these accidents in any society can be specific to that work environment and occupational community. Consistent with various studies (27)(28)(29), this study revealed that although the index of non-organizational factors was estimated to be average, a significant relationship was observed between that and 10 parameters related to occupational accidents. Also, this factor analysis indicated that this index was directly related to some parameters of accidents and inversely related to others.…”
Section: Discussionsupporting
confidence: 88%
“…Due to rapid changes of technology and occupational accidents that impose heavy costs (1,2), new approaches and improving safety management systems seems absolutely necessary, especially in oil industries, which have a high risk of accidents (3).…”
Section: Introductionmentioning
confidence: 99%
“…[22] Research findings indicated that perceived value to donors' satisfaction with path coefficient of 0.65 and service quality to perceived value with path coefficient of 0.43 have highest prediction power and impact, because perceived value is a powerful force in directing operations, attitudes, and judgments in all daily life aspects. [22][23][24][25][26] Since service quality affects perceived value and satisfaction of customers, thus accountability and responsibility of employees of blood transfusion organization, using efficient system and increasing employee capability is recommended. Furthermore, given impact of donors' expectations on perceived value, it can be stated that the model enjoys relatively suitable goodness of fit.…”
Section: Discussionmentioning
confidence: 99%